A sphinx from Kerma in the Karnak Cachette - Hardwick, Tom (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
JE 37845, a statue of a sphinx found in the Karnak Cachette, has evaded secure identification since its discovery. Study of its material allows it definitively to be assigned to the Kerma Culture.